The contribution of energy systems during 15-second sprint exercise in athletes of different sports specializations - Archacki, D.; Zielinski, J.; Pospieszna, B.; Wlodarczyk, M.; Kusy, K. (PeerJ, 2024)
Background Long-term adaptations and ongoing training seem to modify the energy system contribution in highly trained individuals. We aimed to compare the energy metabolism profile during sprint exercise in athletes of different specialties.